Learning styles and their influence on the english language learning with students of 1 st, 2 nd and 3 rd years of bachillerato at unidad educativa anexa a la Universidad Nacional de Loja. Academic period 2012-2013 - Vega Pizarro, Sonia Rosario (2014)
This research entitled “LEARNING STYLES AND THEIR INFLUENCE ON THE ENGLISH LANGUAGE LEARNING WITH STUDENTS OF 1ST, 2ND AND 3RD YEARS OF BACHILLERATO AT UNIDAD EDUCATIVE ANEXA A LA UNIVERSIDAD NACIONAL DE LOJA”. ACADEMIC PERIOD 2012-2013., was developed with the purpose of determining the influence that learning styles have on the development of English language learning The scientific, descriptive, analytical-synthetic and explicative method were used to develop every part of the research. A survey was applied to teachers and students to verify the hypotheses through a logical analysis of the results and the descriptive statistics was used to represent the data in tables and graphs. The results demonstrate that the learning styles have an influence on the learning of English language, because over half of teachers and students are conscious that these styles are the different ways and methods of learning that people use to learn; In addition, the teachers are mindful that the use of didactic resources according to the ways that students learn supports the learning of English language. .